Pengaruh Penggunaan Alat Kontrasepsi Hormonal Terhadap Kejadian Kanker Payudara di Fasilitas Pelayanan Kesehatan - Putri Sukma Wulandari; Amelia Jessica Simanjuntak; Ruth Clara; Edelwise Lasma Estaurina Napitupulu; Nayla Kamilia Fithri (Viva Medika, 2023)
Breast cancer is a common cancer that affects women. There are 2.3 million women suffering from breast cancer globally in 2020, with 68,858 cases from Indonesia. Risk factors include prolonged exposure to endogenous estrogens, late menopause, early menarche, first time giving birth at old age, and exogenous hormones. This study aims to determine the role of hormonal contraception against breast cancer. The literature study was made by analyzing 10 articles published between 2018-2023. Literature searches were conducted through electronic databases, namely PubMed, Garuda and Google Scholar. The results of the study stated that users of hormonal contraceptives have a higher risk of developing breast cancer compared to those who do not use hormonal contraceptives.